Fibroblast-Induced Paradoxical PI3K Pathway Activation in PTEN-Competent Colorectal Cancer: Implications for Therapeutic PI3K/mTOR Inhibition - Conciatori, Fabiana; Salvati, Erica; Ciuffreda, Ludovica; Shirasawa, Senji; Falcone, Italia; Cognetti, Francesco; Ferretti, Gianluigi; Zeuli, Massimo; Del Bufalo, Donatella; Bazzichetto, Chiara; Milella, Michele (Frontiers in Oncology, 2022)
Purpose: Tumor-microenvironment interactions are important determinants of drug resistance in colorectal cancer (CRC). We therefore set out to understand how interactions between genetically characterized CRC cells and stromal fibroblasts might influence response to molecularly targeted inhibitors. Techniques: Sensitivity to PI3K/AKT/mTOR pathway inhibitors of CRC cell lines, with known genetic background, was investigated under different culture conditions [serum-free medium, fibroblasts' conditioned medium (CM), direct co-culture]. Molecular pathway activation was monitored using Western Blot analysis. Immunoprecipitation was used to detect specific mTOR complex activation. Immunofluorescence was used to analyze cellular PTEN distribution, while different mutant PTEN plasmids were used to map the observed function to specific PTEN protein domains. Results: Exposure to fibroblast-CM resulted in increased growth inhibitory response to double PI3K/mTOR inhibitors in PTEN-competent CRC cell lines harboring KRAS and PI3K mutations. Such functional effect was attributable to fibroblast-CM induced paradoxical PI3K/mTORC1 pathway activation, occurring in the presence of a functional PTEN protein. At a molecular level, fibroblast-CM induced C-tail phosphorylation and cytoplasmic redistribution of the PTEN protein, thereby impairing its lipid phosphatase function, and favored the formation of active, RAPTOR-containing, mTORC1 complexes. However, PTEN's lipid phosphatase function appeared to be dispensable, while complex protein-protein interactions, also involving PTEN/mTOR co-localization and subcellular distribution, were crucial for both mTORC1 activation and sensitivity to double PI3K/mTOR inhibitors. Data interpretation: Microenvironmental cues, in particular soluble factors produced by stromal fibroblasts, profoundly influence PI3K pathway signaling and functional response to specific inhibitors in CRC cells, depending on their mutational background and PTEN status.